Progression of elite New Zealand and Australian junior athletes to senior representation - Hollings, S.; Hume, P (New Studies in Athletics, 2011)
There is a reasonable probability that athletes who have achieved a high level of success as a junior will go on to be successful seniors. This study tested the idea by following Australian and New Zealand athletes taking part in the IAAF World Junior Championship (WJC) from 1986 to 2006 through to senior global and Commonwealth Games performances - or otherwise.